Aprovechamiento de los desechos de aceites vegetales generados por el comedor universitario de la U.N.T. para la producción de biodiesel - Castillo Vergara, Benson Neil (2017)
The main problems of environmental pollution are mainly in the air and water. In the air, industrial and vehicle emissions have increased the concentration of gases and particulate pollutants in the atmosphere; On the other hand, the degradation of water is caused by the discharge of pollutants between them, the oils that usually come from industrial effluents and from domestic drains, as is the case of used vegetable oils. In the UNT these two environmental problems are caused by the discharge to the drain of 13.8 kg weekly of used vegetable oil. In order to find a solution, it was proposed to take advantage of these discarded oils from the university dining room to produce a clean fuel that could replace diesel. Biodiesel comes from the transesterification of vegetable oils, where the fatty acids that make up the triglycerides (in the presence of a KOH or NaOH catalyst and high temperatures) react with an alcohol (methanol) to produce methyl esters and release glycerol. To obtain these products a series of intermediate reactions are generated in which the initial triglyceride passes to diglyceride, monoglyceride and finally to glycerol, producing a methyl ester in each reaction. The final product generally contains impurities so it is necessary to wash it to avoid corrosion and residue problems during use in diesel engines. In spite of this, the use of biodiesel as diesel additive has environmental advantages because it does not generate SO2 during its combustion and also reduces the emission of contaminating particles to the environment. This research was divided into five parts, the first was to characterize used vegetable oil to determine its acidity index; Subsequently at the laboratory level determine the optimum reaction temperature; Then with this temperature find the optimum reaction time as well as the best catalyst; And finally with the products obtained know the quality of the biodiesel evaluating its combustible properties. The amount of used vegetable oil discarded was quantified: 13.8 kg / week. A pre-treatment was performed on the oil which consisted of the removal of solids, dried removal of free fatty acids. For the latter, if the oil used had an acid value (IA) <1% more catalyst should be added to the reaction; However if IA were> 1% an acid esterification would be performed. The acid value obtained was 0.6%, whereby the quantities of catalyst to be used in the treatments were determined: 4.425 g NaOH / L oil and 10.245 g KOHg KOH / L oil. In order to know the optimal reaction temperature, 10 treatments were carried out in the laboratory according to the type of catalyst and temperature level (60 ° C, 50 ° C, 40 ° C, 30 ° C, ambient). Properties were measured for each product, such as drop rate, biodiesel production yield, glycerol yield and density; A factorial arrangement was used in DCA. As there was no gas chromatograph that could have accurately determined the percentage of methyl esters and intermediates in the final result, it was decided to consider the amount of glycerol produced as a determinant to obtain a better product, because it derives from a Higher conversion of triglycerides and fewer intermediate products in biodiesel. For 60 ° C not only better performance was obtained but also a higher fall rate. In the biodiesel reactor 2 baths of 40 L of oil were transesterified at 60 ° C for each type of catalyst; Samples were taken every fifteen minutes to determine the optimum time and best catalyst in the reaction. The resultant products were measured the same properties as on a laboratory scale and the same criterion was used for the amount of glycerol produced to know the best biodiesel production at the time level. In the case of NaOH, the highest production of glycerol was obtained at 150 minutes of reaction but with a yield of 12.6%, however for the reaction catalyzed with KOH, the optimum time was 75 minutes and the yield was 14.6%. This latter catalyst therefore achieves a greater transformation of triglycerides to methyl esters and glycerol. Evaluating the biodiesel production yields with respect to the original used oil, 96.9% (catalyzed with NaOH) and 94.4% (catalyzed with KOH) were obtained. The combustion properties measured in the produced biodiesel were compared with the standards ASTM 6751-03 (B100), being that: the flash point, cetane number, percentage of ash, kinematic viscosity and acidity index, comply with the technical standard; While the percentage of water and sediments (for the product with NaOH), and percentage of conradson coal (for both catalysts), do not comply with the standards, so the product would still contain impurities due to a possible deficiency in The washing